Mild hypothermia (33°C) increases the inducibility of atrial fibrillation: An in vivo large animal model study. Issue 7 (15th May 2018) - Manninger, Martin; Alogna, Alessio; Zweiker, David; Zirngast, Birgit; Reiter, Stefan; Herbst, Viktoria; Maechler, Heinrich; Pieske, Burkert M.; Heinzel, Frank R.; Brussee, Helmut; Post, Heiner; Scherr, Daniel
Abstract: Objective: Application of therapeutic mild hypothermia in patients after resuscitation, often accompanied by myocardial infarction, cardiogenic shock, and systemic inflammation may impact on cardiac rhythm. We therefore tested susceptibility to atrial arrhythmias during hyperthermia (HT, 40.5°C), normothermia (NT, 38.0°C), and mild hypothermia (MH, 33.0°C). Methods: Nine healthy, anesthetized closed‐chest landrace pigs were instrumented with a quadripolar stimulation catheter in the high right atrium and a decapolar catheter in the coronary sinus. Twelve‐lead surface electrograms were recorded and core body temperature was altered to HT, NT, and MH using external warming or intravascular cooling. Repetitive measurements of effective atrial refractory period (AERP), atrial fibrillation (AF) inducibility, and electrocardiogram (ECG) parameters at different heart rates were performed. Results: During MH, AERP was significantly longer while the inducibility of AF was significantly higher compared to NT and HT (median [range]: HT 18 (0, 80)%; NT 25 (0, 80)%; MH 68 (0, 100)%; P < 0.05 MH vs NT+HT). Mean AF duration did not differ between groups. Arterial potassium levels decreased with falling temperatures (HT: 4.2 ± 0.1 mmol/L; NT: 4.0 ± 0.2 mmol/L; MH: 3.5 ± 0.1 mmol/L; P < 0.001). Surface ECGs during MH showed reduced spontaneous heart rate (HT: 99 ± 13 beats/min; NT: 87 ± 15 beats/min; MH: 66 ± 10 beats/min; P < 0.05), increased PQ, stim‐Q, and QT intervals (P < 0.01) but no change in QRS duration or time from peak to end of the T wave interval. Conclusion: Our data imply that MH represents an arrhythmic substrate rendering the atria more susceptible to AF although conduction times as well as refractory periods are increased. Further investigations on potential electrophysiological limits of therapeutic cooling in patients are required.